ANALYZING CORPORATE CULTURE IN HOTEL COMPANY USING ORGANIZATIONAL CULTURE, ASSESSMENT INSTRUMENT (OCAI) : CASE STUDY X HOTE IN JAKARTA - Lumbantoruan, Theresia Melisa; Zainal, Munawaroh; Prasetyawati, Dea (Academic Research Centre Services, 2013)
Organizational Culture Assessment Instrument well-known as OCAI commonly uses to describe the type of culture in a company. Using values framework as and instrument, this research attempt to find out what type of culture base on four culture type of Cameron and Quinn: Clan Hierarchy, Adhocracy and Market. Asking `89 of hotel staff respondent and applying on the framework, hotel staff exhibited Hierarchy culture as dominant in current situation and they preferred Clan culture for the future. This discrepancies between the current and preferred culture indicates that a change in culture, especially to clan culture. Result of culture perspectives between levels of hierarchy indicates staff and managers preferred to have clan culture. Culture profile on Six Key Dimensions of Culture (SKDC). Result showed that the overall scores and ranking were almost congruent in the current culture of all aspects. The preferred culture were reasonably congruent, Having clan culture dominating all aspects.